2013
DOI: 10.1177/1049909113486170
|View full text |Cite
|
Sign up to set email alerts
|

Completion of Advance Directives Among Low-Income Older Adults

Abstract: This study examined the prevalence of completion of advance directives (ADs) and the effects of race/ethnicity on AD completion using a cross-sectional design. Low-income older adults (n = 256) who were residents of supportive housing facilities or members of a senior center were interviewed in person. About 20% of the participants had completed ADs. Knowledge and attitudes toward ADs, income, and previous experience in an intensive care unit significantly predicted the completion of ADs after controlling for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
71
2
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(84 citation statements)
references
References 40 publications
(60 reference statements)
9
71
2
2
Order By: Relevance
“…, Johnson et al . , Ko & Lee , ). This may mean that there are other factors widening an ethnic difference in actual AD completion such as availability and accessibility to AD information and opportunities to discuss ADs in the healthcare setting.…”
Section: Discussionmentioning
confidence: 99%
“…, Johnson et al . , Ko & Lee , ). This may mean that there are other factors widening an ethnic difference in actual AD completion such as availability and accessibility to AD information and opportunities to discuss ADs in the healthcare setting.…”
Section: Discussionmentioning
confidence: 99%
“…Johnson and colleagues have reported that racial differences in advance directive possession are no longer significant after adjustment for cultural beliefs and values, sampling 205 older adults recruited from one university health center; Ko and Lee have reported that Latino-white differences in advance directive possession are explained by differences in knowledge, sampling 256 older adults from the same urban area. 10,11 Carr reported that black-white differences in advance directive possession are limited to those of low socioeconomic status, although this national sample of 2111 adults was limited to those in stable romantic partnerships (potentially screening for high socioeconomic status and more conservative cultural values). 22 In our study, participants who reported Catholic and Evangelical religious affiliations were less likely than mainline Protestants to have advance directives, even after adjusting for personal health values.…”
Section: Discussionmentioning
confidence: 99%
“…On this alternative hypothesis, race and ethnicity are merely proxies for cultural beliefs and religious values that influence individuals' willingness to undertake advance care planning. 10,11 In support of this hypothesis, black and Hispanic Americans are more likely than white Americans to say religion is very important in their lives 6,10 and black Americans are more likely to endorse the statement that their health outcomes are determined by God. 12,13 Furthermore, whereas advance directives are often used to limit life-sustaining treatment, black and Hispanic Americans are more likely to desire life-sustaining treatment despite poor prognosis.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…However, despite advanced care planning education efforts, completion of ADs is relatively low, with only one third to one half of older adults completing ADs (Ko & Lee, 2014). Clinicians encounter and support clients and their families with the associated comorbidities of aging and the loss of social networks.…”
Section: Resultsmentioning
confidence: 98%